Tonic Control of Secretory Acid Sphingomyelinase Over Ventral Hippocampal Synaptic Transmission and Neuron Excitability - Lin, Chih-Hung; Kornhuber, Johannes; Zheng, Fang; Alzheimer, Christian (Frontiers in Cellular Neuroscience, 2021)
The acid sphingomyelinase (ASM) converts sphingomyelin into ceramide. Recent work has advanced the ASM/ceramide system as a major player in the pathogenesis of ma-jor depressive disorder (MDD). Indeed, ASM activity is enhanced in MDD patients and antidepressant drugs like fluoxetine act as functional inhibitors of ASM. Here, we em-ployed the specific ASM inhibitor ARC39 to explore the acute effects of the enzyme on hippocampal synaptic transmission and cell excitability in adult mouse brain slice preparations. In both field potential and whole-cell recordings, ARC39 (1-3 µM) en-hanced excitatory synaptic input onto ventral hippocampal CA1 pyramidal cells. The specificity of drug action was demonstrated by its lacking effect in slices from ASM knockout mice. In control condition, ARC39 strongly reduced firing in most CA1 pyram-idal cells, together with membrane hyperpolarization. Such pronounced inhibitory ac-tion of ARC39 on soma excitability was largely reversed when GABAA receptors were blocked. The idea that ARC39 recruits GABAergic inhibition to dampen cell excitability was further reinforced by the drug´s ability to enhance the inhibitory synaptic drive on-to pyramidal cells. In pyramidal cells that were pharmacologically isolated from synaptic input, the overall effect of ARC39 on cell firing was inhibitory, but some neurons dis-played a biphasic response with a transient increase in firing, suggesting that ARC39 might alter intrinsic firing properties in a cell-specific fashion. Because ARC39 is charged at physiological pH and exerted all its effects within minutes of application, we propose that the neurophysiological actions reported here are due to the inhibition of secretory rather than lysosomal ASM. In summary, the ASM inhibitor ARC39 reveals a tonic control of the enzyme over ventral hippocampal excitability, which involves the intrinsic excitability of CA1 pyrami-dal cells as well as their excitatory and inhibitory synaptic inputs.